Primary Tuberculosis of Tonsils: A Case Report - Eroğlu, Orkun; Yağmahan, Mehmet Salih; Artaş, Gökhan; Karlıdag, Turgut (My University, 2018)
Tuberculosis is a contagious disease mainly caused by Mycobacterium tuberculosis, often seen in underdeveloped or developing countries, and typically involves the lungs. Isolated tonsillar tuberculosis is a very rare clinical entity in the absence of active pulmonary tuberculosis. Tonsillar tuberculosis is an extremely rare form of extrapulmonary tuberculosis that frequently imitates tonsillar malignancy, particularly in elderly individuals. Clinically, it is very difficult to differentiate it from tonsillar malignancy; therefore, histopathological examination of the tissue is necesssary for the diagnosis of tonsillar tuberculosis, and antitubercular therapy is adequate for successful resolution. In the present study, we report a primary form of tonsillar tuberculosis in a 51-year-old female without pulmonary tuberculosis.
Keywords: Genel ve Dahili Tıp; Mikrobiyoloji; Kulak; Burun; Boğaz